Ecological planning : a historical and comparative synthesis - Ndubisi, Forster, 1955- (Center books on contemporary landscape design., 2002)
"Should be read by all institutional and public choice economists who work toward solving problems associated with human use of the natural environment."--Journal of Economic Issues